La política de descentralización educativa en la Argentina de los 90 - Rodrigo, Lucrecia (Revista Complutense de Educación, 2006)
This paper aims to evaluate the way in which the educational decentralization process was conducted in Argentina during the 1990s. The educational decentralization reform constituted a discontinuity within the traditional form the educational system was organised in the country. In the first part of this article we will look in detail at the educational decentralization policy from a genealogical perspective in order to account for a certain historical continuity. In the second part, we will turn to examine how the urgency of the national State to diminish the national cost in education was one of the central variables that influenced in the definition of the decentralization strategy. Finally, we will discuss some of the main critics and current debates on the results of this policy in Argentina.